Imaging and condition diagnosis of underground sewer liners via active and passive infrared thermography: A case study in Singapore. (February 2019) - Sham, Janet F.C.; Lai, Wallace W.L.; Chan, Wing; Koh, Chee Lin
Abstract: This paper presents a case study of customizing an in-house built In-pipe Infrared Thermographic System (IPITS), which makes use of thermo-images for imaging and diagnosis of pipe crown condition in underground sewer pipelines. Active and passive infrared thermography (IRT) were attempted in two gravity sewer pipes in Singapore in July 2017. The results show that images captured with active IRT (with heating) can image and reveal invisible lining defects not readily revealed by traditional visual inspection using CCTV. These defects include bubbles, wrinkling and delamination, or construction details (like anchor knobs in HDPE material), for which sizes were estimated using an image processing algorithm customized in an in-house program. While images captured by passive IRT (without heating) can be used to identify suspected water seeping points, this paper also reports the design of instrumentation and appropriate parameter settings. The results of this case study are believed to pave the way for parallel inspections using a combination of CCTV and infrared cameras.